Analisis Framing Pemberitaan Program Makan Gratis Prabowo Subianto Di Media Online - Vanti, Mey Esa Dwi; Octaviani, Vethy; Maryaningsih, Maryaningsih (UNIVED PRESS, Universitas Dehasen Bengkulu, 2024)
online media is a combination of all components of text, video, audio and photos. Political news becomes a medium for the public or the press itself to convey political messages to political actors, both support and criticism. Prabowo Subianto is the Minister of Defense of the Republic of Indonesia who is running for President in 2024. One of Prabowo's programs if elected President is the Free Meal Program. This program was suddenly widely reported by the media, various reports about the program were in online media such as online media detik.com and VIVA.co.id. This research was conducted to analyze the online media detik.com and VIVA.co.id in framing news about Prabowo Subianto's Free Meal Program using the framing analysis approach model of Zhongdang Pan and Gerald M. Kosicki. This research is descriptive qualitative research. The method used in this research is the framing analysis model of Zhongdang Pan and Gerald M. Kosicki which uses a framing device consisting of four structures, namely, Syntactic Structure, Script Structure, Thematic Structure and Rhetorical Structure. The results of this research, detik.com media, in reporting on Prabowo Subianto's Free Meal Program, supports this program. This can be shown in the headline of the news. In the first news title, detik.com appears to explain Prabowo Subianto's Free Meal Program, which means that detik.com media reports on the positive side of the program. detik.com frames the news by selecting news sources, selecting quotes that support statements and information provided in the news. VIVA.co.id put the parties who gave counter statements and criticized the program, VIVA.co.id wants to show the public that is where the controversy is. Political news regarding the Prabowo Subianto Free Meal Program on the online media detik.com and VIVA.co.id has an impact on the knowledge, attitudes and perspective of the public who see the reality of the news framing of the program.